Studies on heterosis, correlation and genetic advance parameters for seed yield and its related traits in Indian mustard [Brassica juncea (L.) Czern and Coss.]: Studies on heterosis, correlation and genetic advance parameters for seed yield and its related traits in Indian mustard [Brassica juncea (L.) Czern and Coss.] - MOHD SALMAN,; MAHAK SINGH,; HARSHIT TRIPATHI,; PAWAN KUMAR,; SWAPNIL DWIVEDI,; SURENDRA KUMAR,; R P VYAS, (Journal of Oilseeds Research, 2020)
Twenty eight genotypes (21 F1 + 7 parents) of Indian mustard were evaluated for 10 traits viz., days to 50% flowering, days to maturity, plant height (cm), length of main raceme (cm), number of siliquae/plant, number of primary branches/plant, number of secondary branches/plant, oil content (%), 1000-seed weight (g) and seed yield/plant (g). Analysis of variance revealed that the genotypes differed genetically for all the characters and thus has helped in selection of parents for the breeding programmes.